2023
DOI: 10.1002/mdc3.13722
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of GBA and LRRK2 on Mood Disorders in Parkinson's Disease

Abstract: BackgroundBackground: Mood disorders have emerged as major non-motor comorbidities in Parkinson's disease (PD) even at the prodromal stage of the disease. Mutations in the LRRK2 and GBA genes are common among Ashkenazi Jews, with more severe phenotype reported for GBA-PD. Objective Objective: To explore the association between genetic status and mood related disorders before and after diagnosis of PD and the association between mood-related medications, phenotype, and genetic status. Methods Methods: Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previous studies assessing anxiety in GBA-associated PD were mostly cross-sectional studies, and GBA variant carriers presented with a high prevalence of anxiety ( DeBroff et al, 2023 ). A few studies using univariable Kaplan–Meier survival analysis demonstrated that the GBA-PD group developed anxiety earlier than the idiopathic PD group ( Pachi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies assessing anxiety in GBA-associated PD were mostly cross-sectional studies, and GBA variant carriers presented with a high prevalence of anxiety ( DeBroff et al, 2023 ). A few studies using univariable Kaplan–Meier survival analysis demonstrated that the GBA-PD group developed anxiety earlier than the idiopathic PD group ( Pachi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of this longitudinal data from a well-designed cohort, our linear mixed model and multivariable Cox regression model showed that GBA variant carriers experienced more than 57% greater annual increase in STAI total anxiety score and faster progression in anxiety compared with non-carriers. Previous studies assessing anxiety in GBA-associated PD were mostly cross-sectional studies, and GBA variant carriers presented with a high prevalence of anxiety (DeBroff et al, 2023). A few studies using univariable Kaplan-Meier survival analysis demonstrated that the GBA-PD group developed anxiety earlier than the idiopathic PD group (Pachi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In idiopathic Parkinson’s, symptoms of anxiety and depression are more prevalent in women than in men (Leentjens et al, 2011; Cui et al, 2017). Although the prevalence of anxiety and depression in human LRRK2 mutation carriers is similar to that in idiopathic Parkinson’s (Gaig et al, 2014; San Luciano et al, 2017; Chen et al, 2020b; DeBroff et al, 2023), it is less clear whether there are sex differences in psychiatric symptoms among manifesting LRRK2 G2019S carriers. One study suggests that depression severity may be similar in male and female mutation carriers (San Luciano et al, 2017), which aligns with the equal penetrance of the mutation in male and female carriers (Marder et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The G2019S mutation in LRRK2 (encoding leucine-rich repeat kinase 2) is among the most common genetic risk mutations for familial and sporadic Parkinson’s (Kluss et al, 2019). LRRK2 G2019S produces late-onset Parkinson’s that is clinically similar to idiopathic forms, including prodromal anxiety and depression in non-manifesting mutation carriers (Shanker et al, 2011; DeBroff et al, 2023). Genetic, pathological, and preclinical studies suggest that dysregulated LRRK2 may be part of a common pathological mechanism (Kluss et al, 2019; Rocha et al, 2022; Peter and Strober, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite therapeutic intervention, PD patients with LRRK2 gene mutations and mood disorders have considerably high depression and anxiety rates. PD patients with mood-related disorders experience high rates of anxiety and depression [ 160 ]. In this context, clinical vigilance for depression screening for patients known to carry these mutations is needed.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%